The Move More Scholars Institute: A State Model of the Physical Activity and Public Health Practitioners Course - Lori Schneider, MA, CHES; Dianne Ward, EdD; Carolyn Dunn, PhD; Amber Vaughn, MPH; Jimmy Newkirk; Cathy Thomas, MAEd, CHES (Centers for Disease Control and Prevention, 2007)
Physical activity has been identified as a public health priority. In response, training and professional development opportunities have been created to increase the capacity of public health practitioners to address this issue. Currently, training resources are primarily reaching national- and state-level professionals. Local-level physical activity and public health practitioners can also benefit from these resources. The Move More Scholars Institute, a 4-day training course for community-based physical activity practitioners in North Carolina, was developed for local practitioners. This article will describe the planning of, implementation of, and initial response to the Move More Scholars Institute.